Development of a new flippase-dependent mouse model for red fluorescence-based isolation of KRASG12D oncogene-expressing tumor cells - Hrckulak, Dusan; Onhajzer, Jakub; Krausova, Michaela; Stastna, Monika; Kriz, Vitezslav; Janeckova, Lucie; Korinek, Vladimir (Transgenic research, 2025)
Proto-oncogene KRAS, GTPase (KRAS) is one of the most intensively studied oncogenes in cancer research. Although several mouse models allow for regulated expression of mutant KRAS, selective isolation and analysis of transforming or tumor cells that produce the KRAS oncogene remains a challenge. In our study, we present a knock-in model of oncogenic variant KRASG12D that enables the "activation" of KRASG12D expression together with production of red fluorescent protein tdTomato. Both proteins are expressed from the endogenous Kras locus after recombination of a transcriptional stop box in the genomic DNA by the enzyme flippase (Flp). We have demonstrated the functionality of the allele termed RedRas (abbreviated KrasRR) under in vitro conditions with mouse embryonic fibroblasts and organoids and in vivo in the lung and colon epithelium. After recombination with adenoviral vectors carrying the Flp gene, the KrasRR allele itself triggers formation of lung adenomas. In the colon epithelium, it causes the progression of adenomas that are triggered by the loss of tumor suppressor adenomatous polyposis coli (APC). Importantly, cells in which recombination has successfully occurred can be visualized and isolated using the fluorescence emitted by tdTomato. Furthermore, we show that KRASG12D production enables intestinal organoid growth independent of epidermal growth factor (EGF) signaling and that the KRASG12D function is effectively suppressed by specific inhibitor MRTX1133.
Keywords: protoonkogenní proteiny p21(ras); modely nemocí na zvířatech; DNA-nukleotidyltransferasy; KRAS oncogene; Intestinal organoids; Colon cancer; nádory plic; červený fluorescenční protein; Lung Neoplasms; Gene Knock-In Techniques; Red Fluorescent Protein; MRTX1133 inhibitor; Gene targeting; DNA Nucleotidyltransferases; luminescentní proteiny; Animals; genový knockin; myši transgenní; zvířata; Disease Models, Animal; myši; Luminescent Proteins; Proto-Oncogene Proteins p21(ras); Mice; Lung cancer; Mice, Transgenic